The study on serum oxidized low-density lipoprotein and homocysteine as cardiovascular risk markers in subclinical hypothyroidism patients - Wang, Qian; Zhang, Xiaonyun; Wu, Fan; Qi, Xinkun (Frontiers in Endocrinology, 2026)
PurposeHypothyroidism, the most prevalent endocrine disorder globally, is associated with increased cardiovascular risk. This study aims to evaluate cardiovascular risk factors—including serum oxidized low-density lipoprotein (ox-LDL), serum homocysteine (Hcy), and lipid profiles—and their correlations with thyroid-stimulating hormone (TSH) levels. Early identification of these risk predictors may reduce the incidence and mortality of cardiovascular disease in hypothyroid patients.Patients and methodsThis cross-sectional study included 676 participants. Subjects were stratified into four groups: three corresponding to TSH quartiles within the reference range and a fourth comprising subclinical hypothyroidism (SCH) patients with TSH levels above this range. All participants underwent physical examinations and provided fasting blood samples for measurement of TSH, free thyroxine (FT4), free triiodothyronine (FT3), blood glucose, triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), apolipoprotein A1 (ApoA1), apolipoprotein B (ApoB), lipoprotein(a) [Lp(a)], ox-LDL, and Hcy.ResultsAcross the four subgroups, LDL-C, ApoB, ox-LDL, and Hcy levels exhibited significant increasing trends (all p < 0.05; specific p = 0.01, p = 0.01, p < 0.01, p < 0.01, respectively), whereas HDL-C decreased significantly (p < 0.01). Specifically, compared to the T1 subgroup (TSH: 0.27-1.58 mIU/L), the SCH subgroup (TSH ≥ 4.20 mIU/L) had significantly higher levels of ox-LDL (1.78 ± 0.49 ng/mL vs. 1.05 ± 0.68 ng/mL, p < 0.01) and Hcy (9.87 (interquartile range (IQR): 8.45-11.42) μmol/L vs. 9.22 (IQR: 8.11-10.11) μmol/L, p < 0.01), and lower levels of HDL-C (1.29 ± 0.36 mmol/L vs. 1.43 ± 0.39 mmol/L, p < 0.01). After adjusting for age and sex, TSH levels demonstrated positive correlations with body mass index (BMI), triglycerides, total cholesterol, LDL-C, ApoB, ox-LDL, and Hcy (all p < 0.05), and a negative correlation with HDL-C (p = 0.01). Multiple linear regression analysis revealed that TSH levels were independently associated with elevated ox-LDL (β = 0.18, p < 0.01) and Hcy (β = 0.11, p < 0.01), and reduced HDL-C (β = −0.16, p = 0.01).ConclusionThe observed correlations between ox-LDL, Hcy, and dyslipidemia in subclinical hypothyroidism may indicate a proatherogenic state. Elevated ox-LDL and Hcy emerge as independent factors associated with accelerated atherosclerosis in this condition.